Hubungan antara Self-Compassion dan Resiliensi pada Mahasiswa Perantau Tingkat Akhir - Adisya, Syaila Rania; Satiadarma, Monty P; Subroto, Untung (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
Final-year students living away from home often face various challenges. In dealing with these challenges, students need resilience in order to overcome them effectively. Resilience is the ability to face and recover from difficulties with strength (Rutter, 2006). In developing resilience, self-compassion plays an important role. Self-compassion is a kind and understanding attitude toward oneself when facing challenges (Neff, 2003). This study aims to explore the relationship between self-compassion and resilience among final-year students living away from home. This research uses a correlational quantitative method with purposive sampling technique. The research subjects are 360 final-year students in Jakarta who are from outside the Jabodetabek area. The measurement tools used are the Self-Compassion Scale (SCS) and the Connor-Davidson Resilience Scale (CD-RISC), both of which have been translated. Data analysis was performed using Spearman's correlation test, and the results show a significance value of 0.001 and a correlation value of 0.438, indicating a positive relationship between self-compassion and resilience. This means that the greater the self-compassion, the greater the resilience.